Innate Immune Activity in Glomerular Podocytes - Xia, Hong; Bao, Wenduona; Shi, Shaolin (Frontiers in Immunology, 2017)
Glomerular podocytes are specialized in structure and play an essential role in glomerular filtration. In addition, podocyte stress can initiate glomerular damage by inducing the injury of other glomerular cell types. Studies have shown that podocytes possess the property of immune cells and may be involved in adaptive immunity. Emerging studies have also shown that podocytes possess signaling pathways of innate immune responses and that innate immune responses often result in podocyte injury. More recently, mitochondrial-derived damage-associated molecular patterns (mtDAMPs) have been shown to play a critical role in a variety of pathological processes in cells. In the present mini-review, we summarize the recent advances in the studies of innate immunity and its pathogenic role in podocytes, particularly, from the perspective of mtDAMPs.